Feasibility Analysis of Captive Power Generation using Renewable Resources in Mangalore - Shivarudraswamy, R.; sreenivasa rao, Potty; Faisal Kamal, Md.; Utkarsh, Kumar (International Journal of Engineering and Technology, 2018)
Smart cities are considered to build a strong and intelligent infrastructure with sustainable environment. It would be impossible to build an efficient Infrastructure without reliable energy source. Under the mandate of the smart cities, 10 per cent of the total energy consumption of the cities must be met by renewables. However, Indiaâ€™s challenges with harnessing solar energy are unique. For example, accumulation of dust on solar panels and high per unit cost of energy are some of the challenges the renewable energy industry in India faces. Thus, there is a need for supporting solar energy with other sources of renewable energy considering its limitations. Hence, the proposed study is aimed at understanding the feasibility of utilizing renewable energy resources to produce power which can be coupled with proposed solar energy to be produced to provide uninterrupted electric power requirements of Mangalore City which otherwise, draws its power requirements largely from State owned Mangalore Electric Supply Company (MESCO). As far as production of electric energy using renewable ener.gy resources by Mangalore Corporation is concerned it can generate power on Biogas, Wind and Tidal. Garbage which they collect from citizens, commercial establishments and industrial unitsÂ Â